STRATEGIES OF IMPLEMENTATION OF EDUCATION TECHNOLOGY IN MADRASAH - Siti Maryam; Haya; Hosaini (Adisam Publisher, 2024)
The research aims to investigate the strategy of implementation of educational technology in Madrasah, its models and challenges. This research uses literary research methods by searching for references that match the context of the research. Research results show that major obstacles to the implementation of educational technology include inadequate technological infrastructure, a lack of technological literacy among teachers and students, and budget constraints. However, several effective strategies have been identified to address these challenges, including teacher capacity development through technology training, collaboration with stakeholders for resource support, and the use of open-source technology as a cost-effective solution. The research emphasizes the importance of a holistic approach in the planning and implementation of educational technology in the madrasah, which not only focuses on the technical aspects, but also on the development of the competence of teachers and students, as well as adaptation to local social and economic conditions. So, the findings of this research require policies that support the integration of educational technology in the madrasah and closer cooperation between governments, educational institutions, and communities to maximize the benefits of technology in learning.